The Saint Mary's Rape Chant: A Discourse Analysis of Media Coverage. Issue 1 (1st March 2021) - Anderson, Lyndsay; Gonick, Marnina
Abstract: In September 2013 student leaders at Saint Mary's University in Halifax, Nova Scotia, used a chant about the rape of underage girls as part of an Orientation Week activity for new students. The incident garnered national and international media coverage. In this article, we analyze and critique a selection of Canadian media articles published in the weeks after the rape chant was used. We draw on feminist analysis of post-feminism and the sexualization of youth cultures to show how, in their struggle to make sense of the incident, the media critique reiterates harmful discourses of youth, gender and sexuality while undermining deeper understanding of rape culture.